If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(7x + -12) + 2(-6 + -10x) = -10x + 3x Reorder the terms: -5(-12 + 7x) + 2(-6 + -10x) = -10x + 3x (-12 * -5 + 7x * -5) + 2(-6 + -10x) = -10x + 3x (60 + -35x) + 2(-6 + -10x) = -10x + 3x 60 + -35x + (-6 * 2 + -10x * 2) = -10x + 3x 60 + -35x + (-12 + -20x) = -10x + 3x Reorder the terms: 60 + -12 + -35x + -20x = -10x + 3x Combine like terms: 60 + -12 = 48 48 + -35x + -20x = -10x + 3x Combine like terms: -35x + -20x = -55x 48 + -55x = -10x + 3x Combine like terms: -10x + 3x = -7x 48 + -55x = -7x Solving 48 + -55x = -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 48 + -55x + 7x = -7x + 7x Combine like terms: -55x + 7x = -48x 48 + -48x = -7x + 7x Combine like terms: -7x + 7x = 0 48 + -48x = 0 Add '-48' to each side of the equation. 48 + -48 + -48x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + -48x = 0 + -48 -48x = 0 + -48 Combine like terms: 0 + -48 = -48 -48x = -48 Divide each side by '-48'. x = 1 Simplifying x = 1
| (-2y^2)(4y)= | | z^2+3=4z | | -15x-1/3= | | z^2+3=3z | | q^2+19=20q | | 6x-3=4x+13 | | k/5.2+81.9=47.2 | | 14.5+x=6.2 | | x+15=-34 | | 4x^2-7=71 | | 2a^-1+3b^-2/a^-1-b^-1 | | x^4+14x^2+49= | | x^4-14x^2+49= | | (9x+7)(4x^2+5x+8)= | | -11(8p+4)=-11(p+11) | | -3x+2(-4)=10 | | 35p^6q^3/49p^6q^2 | | X+1/3x=36 | | 30/14=m/1.54 | | x^2+2x=26.01 | | 4(3x-4)=2(x-2) | | 9x-4=2(x+3) | | 3(5x-6)=-48 | | 4/3v-4/3 | | 26x+144x=0 | | 1/24*65^2=150 | | 14x-25x=9x | | -6(1x+5)=-72 | | -5.5x+0.56=-1.64 | | 1/24/65^2=150 | | 6x^2/3x^2=0 | | 5x^2-10lx-15=0 |